The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1210/jcem-55-2-311
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Metabolite Excretion during Childhood and Puberty

Abstract: Daily urinary excretion of conjugated 6-hydroxymelatonin, the major metabolite of the pineal hormone melatonin, has been determined in 54 boys and 47 girls (aged 3-16 yr) and 20 normal adults to determine whether a change in melatonin production is seen during the maturation of reproductive function in humans. There was no correlation between daily excretion rates and age in children, and the excretion rates were similar to those in adults. In addition, children of all ages had normal circadian patterns of 6-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
16
0
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 14 publications
8
16
0
1
Order By: Relevance
“…Waldhauser et al [5] reported maxi mum nighttime blood MLT concentrations during early childhood (1-5 years) and an exponential decrease there after. Fellenberg et al [8], Tetsuo et al [ 11 ], and Young et al [12] studied the MLTS excretion in children from 2 or 3 years to adulthood with different methods and obtained results similar to ours. Kennaway et al [21] who studied the MLTS excretion during the 1st year of life in preterm and term babies also found an increase of the MLTS excretion after 4-6 months of age in the same range as we did.…”
Section: Discussionsupporting
confidence: 82%
“…Waldhauser et al [5] reported maxi mum nighttime blood MLT concentrations during early childhood (1-5 years) and an exponential decrease there after. Fellenberg et al [8], Tetsuo et al [ 11 ], and Young et al [12] studied the MLTS excretion in children from 2 or 3 years to adulthood with different methods and obtained results similar to ours. Kennaway et al [21] who studied the MLTS excretion during the 1st year of life in preterm and term babies also found an increase of the MLTS excretion after 4-6 months of age in the same range as we did.…”
Section: Discussionsupporting
confidence: 82%
“…To date little information is available to support any of these explanations. The finding of similar excretion of 6-hydroxymelatonin in children and adults has been in terpreted to signify that melatonin production by the pi neal gland does not change during growth [40]. Based on that observation, the higher melatonin plasma concentra tions found in younger individuals were attributed to a smaller volume of distribution [23].…”
Section: Discussionmentioning
confidence: 97%
“…and increases between 3 and 12 months of age [5]. Uri nary 6-sulphatoxymelatonin (corrected for body surface area) is low until 6-10 weeks after birth, peaks between 4 and 7 years and then drops [6], though no drop is seen if changes in body surface area or size are not taken into account [7], Waldhauser et al [8] looked at night-time melatonin levels in 367 men and women, aged from 1 to 90 years. There were high levels in childhood peaking at 1-3 years of age, considerably lower levels between 15 and 20, and then a moderate decline until old age.…”
mentioning
confidence: 99%